PENGARUH SUKUK KORPORASI DAN REKSA DANA SYARIAH TERHADAP STRUKTUR PEREKONOMIAN INDONESIA - Surya Tegar Widjiantoro (Jurnal Ilmiah Ekonomi Islam, 2023)
This study uses secondary data obtained from various trusted sites, the data collected for this study is from 2010 to 2021 and this data uses an annual time frame. This study uses multiple regression analysis method with 2 (two) variables X and 1 (one) variable Y. This study was conducted to determine how the influence partially and simultaneously between each variable (Corporate Sukuk and Sharia Mutual Funds). The results of this study indicate that the Corporate Sukuk variable has a significant effect on the Economic Structure and the Sharia Mutual Fund variable has no significant effect on the Economic Structure. This can be proven by the results of the t count of each variable obtained by t count > t table (2.774> 0.7027) and the value of sig < (0.022 < 0.05) for Corporate Sukuk and t count < t table (0.171 < 0.7027 ) and sig > (0.868 > 0.05) for Sharia Mutual Funds.